Beam-steering of a single-element nano-antenna with two transferring dielectric flat lenses - Fatma E. Helmy; Ibrahim I. Ibrahim; Amany M. Saleh (Scientific Reports)
Abstract A novel idea for mechanical beam-steering based on a single hybrid plasmonic nano-antenna (NA) with transferring lenses is presented in this research. Two inhomogeneous rectangular dielectric flat lenses modelled with different materials are used in the switched-beam nano-antenna (NA) to boost and steer radiation in a specific direction by shifting each lens. Firstly, a hybrid plasmonic NA design with two movable lenses is shown. Electromagnetic full-wave simulations examine the performance of this device, and the complete system is numerically evaluated. A conventional elliptical patch NA without lenses produces a gain of up to 10.7 dBi and a return loss of − 14.41 dB. The design with two gradient-index dielectric flat lenses is introduced to enhance antenna performance by improving gain while minimizing beam width. Furthermore, the beam-steering capabilities by displacement of the two lenses according to different positions of lenses along the X and Y-direction. By using the two gradient-index dielectric flat lenses, the gain is increased to 20.3 dBi with an improvement in the return loss reach to -24.9 dB compared with traditional NA. In addition, the beam-steering capabilities were achieved with a range  ± 45° × ± 40° with acceptable average antenna gain, side-lobe levels, and half power beam-width of 18 dBi, − 7.4 dB and 10.7° respectively. Moreover, the PSO algorithm is provided to maximize the pre-specified fitness function.